Disciplinary System and its role in reducing administrative corruption (مجلة أبحاث قانونية, 2023)
The study began by clarifying the concept  of the disciplinary system and its basic elements,  represented in: the violation of the disciplinary system, the disciplinary  sanction,  legal procedures, the disciplinary authority, and  the administrative investigation  that requires research Studying and  ascertaining  the nature of the  object  subject of the violation, and the  guarantees on which it depends is governed and regulated  by legal procedures and  rules that preserve the freedoms and rights of all its parties: the public servant, the  competent authority, and the public of beneficiaries.The study then moved to  explain  the relationship between the role  of the disciplinary system and administrative corruption: material,  moral,  explaining the importance of  using this system as an economic  and social mechanism,  leading to raising the level of performance of   the public employee,  Increasing the efficiency of the State's administrative apparatus,  thereby increasing its capacity to provide the needs of society for goods and services,  which leads to economic and social progress.
Keywords: Disciplinary Offence; Disciplinary Sanction; Public Utilities; Economic Progress